Inside Back Cover: Synthesis of Diverse Polycarbonates by Organocatalytic Copolymerization of CO2 and Epoxides: From High Pressure and Temperature to Ambient Conditions (Angew. Chem. Int. Ed. 4/2022). Issue 4 (29th December 2021) - Zhang, Jinbo; Wang, Lebin; Liu, Shaofeng; Li, Zhibo
Abstract : The synergetic binary phosphazene/triethylborane (TEB) system is highly active and selective towards the ring‐opening alternating copolymerization of CO2 with different epoxides to prepare diverse CO2 ‐based polycarbonates (CO2 ‐PCs). In their Research Article (e202111197), Shaofeng Liu, Zhibo Li, and co‐workers report that this metal‐free organocatalyst can efficiently copolymerize CO2 with cyclohexene oxide under ambient conditions (1 atm pressure and room temperature), which is an environmentally friendly and more carbon‐balanced way toward CO2 utilization.